Fault Tolerant Control for Engine Fuel System with Performance Degradation - Zhang, Xinyuan; Zhang, Yuwei; Wang, Xingjian; Wang, Shaoping (IEEE Conference on Industrial Electronics and Applications (Online), 2025)
In this paper, an adaptive fault-tolerant control (AFTC) strategy is designed for the fuel regulation system of aircraft engines with degraded performance, aiming to avoid saturation and instability problems that may be induced by the rash introduction of control instructions that exceed the system capabilities after the system performance is degraded. A multi-level fault quantification method is first proposed, mapping variations in key system parameters to five discrete fault severity levels. A hierarchical reference-model framework is then established: the open-loop system is linearized around each equilibrium point and closed with a simple segmented PID controller to form the reference models. Simulation studies comparing the step responses of both the reference model and the actual system under all five fault levels demonstrate that the proposed method maintains good stability and satisfactory tracking performance despite increasing fault severity. The results validate the feasibility and robustness of the multi-level reference model-based AFTC approach for fuel regulation systems, offering valuable insights for engineering implementation.